2016
DOI: 10.1007/s00246-016-1512-6
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Tracheostomy in Children Requiring Surgery for Congenital Heart Disease

Abstract: Outcomes after discharge in children requiring tracheostomy after cardiac surgery have not been fully described. A retrospective, single-center study was performed on all children <18 years of age requiring both tracheostomy and surgery for congenital heart disease from January 2002 to May 2015. Forty-six tracheostomies were placed after surgery and four before. Single-ventricle anatomy was present in 12 (33%) patients. Incidence of tracheostomy after heart surgery increased from 0.8% the first half of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 13 publications
10
35
0
3
Order By: Relevance
“…These findings were not related to higher rates of prematurity, lower gestational weights, or younger gestational ages in this group. The findings of increased mortality in infants with CHD are similar to other studies evaluating tracheostomy in pediatric patients of all ages with cardiac disease . For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These findings were not related to higher rates of prematurity, lower gestational weights, or younger gestational ages in this group. The findings of increased mortality in infants with CHD are similar to other studies evaluating tracheostomy in pediatric patients of all ages with cardiac disease . For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease. Several other studies have evaluated in‐hospital mortality after pediatric tracheostomy and reported high rates of mortality in cardiac patients ranging from 22% to 40% . These studies include a wide age range of children, mostly 0‐18 years, with CHD who have various associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations